2020
DOI: 10.1097/ijg.0000000000001673
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Intraocular Pressure With Obesity and Cardiometabolic Risk in a Young Farmworker Population

Abstract: Précis: Intraocular pressure (IOP) was found to be significantly correlated with body mass index (BMI), waist circumference, and diastolic blood pressure (DBP) in a farmworker population located in the southeast Georgia, USA. BMI was correlated with IOP, independent of systemic blood pressures. Purpose: Elevated IOP is a known risk factor for glaucomatous optic neuropathy and is believed to be associated with obesity and cardiometabolic diseases. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Therefore, the systemic factors causing elevated IOP are linked. This result is consistent with many cross-sectional and longitudinal studies where participants with obesity, typically represented by BMI, have experienced elevated IOP 27 28. Obesity has been suspected of increasing IOP by excessive intraorbital adipose tissue, increases in blood viscosity, increased hyperleptinaemia-induced oxidative stress on the trabecular meshwork and outflow facilities and increases in episcleral venous pressure, causing a consequent decrease in the facility of aqueous outflow 11…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the systemic factors causing elevated IOP are linked. This result is consistent with many cross-sectional and longitudinal studies where participants with obesity, typically represented by BMI, have experienced elevated IOP 27 28. Obesity has been suspected of increasing IOP by excessive intraorbital adipose tissue, increases in blood viscosity, increased hyperleptinaemia-induced oxidative stress on the trabecular meshwork and outflow facilities and increases in episcleral venous pressure, causing a consequent decrease in the facility of aqueous outflow 11…”
Section: Discussionsupporting
confidence: 86%
“…SBP is a strong risk factor for EIOP [ 21 , 22 , 23 ]. According to a previous longitudinal prospective study, [ 21 ] for a 10 mmHg increase in SBP and DBP, there was a 0.21 mmHg and 0.43 mmHg increase in IOP, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of epidemiological studies have focused on the connection between obesity and IOP, or ocular hypertension. Various studies have revealed an independent cross-sectional connection between obesity and ocular hypertension using population-based data [ 47 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. A high BMI was found to be a significant risk factor for glaucoma in the Gangnam Eye Study [ 61 ], and a link between high BMI and high IOP was found in the 2008–2010 Korea National Health and Nutrition Examination Survey [ 62 ].…”
Section: Glaucoma: Intraocular Pressure/ocular Hypertension and Relat...mentioning
confidence: 99%
“…As aforementioned, several studies have reported that obesity has a positive correlation with increased IOP and an increased risk of developing glaucoma [ 46 , 49 , 51 , 52 , 65 , 123 , 124 ]. In young adults in particular, obesity could be a potential risk factor for glaucoma [ 63 ].…”
Section: Microbiome Dysbiosis At the Intersection Of Obesity And Glau...mentioning
confidence: 99%
See 1 more Smart Citation